Corporate social responsibility disclosures and board structure: evidence from Malaysia - Abdul Razak, Shazrul Ekhmar; Mustapha, Mazlina (Penerbit Universiti Teknologi Malaysia, 2013)
Corporate governance is a critical element in driving excellence in corporate social responsibility (CSR). One of the important cornerstones of corporate governance is board of directors. Thus, this study attempts to examine the effect of this board structure on corporate social responsibility disclosures of public listed companies in Malaysia. Data for the study was collected using secondary source. CSR disclosure index was developed in an attempt to examine the CSR disclosure in the four dimensions as specified by the Bursa Malaysia. The four dimensions are environmental, community, workplace and marketplace. Multiple regression analysis was employed to analyze the data. The result shows that managerial ownership is significant and negatively influences the CSR disclosure in Malaysian listed companies. The other board variables appear to have the expected direction of the hypotheses, but are not significant.